ANALYSIS OF MARKETING STRATEGIES IN MAINTAINING PRODUCT LIFE CYCLE AT PT. SIANTAR TOP,TBK - Sembiring, Ruwina Puspita; Hidayat, Rahmat (SEAN Institute, 2023)
This research was conducted at PT. Siantar Top, Tbk which is on Jalan Pematang Siantar No 13, Ujung Serdang, Tj Morawa, Deli Serdang Regency North Sumatra. The purpose of this study is to determine the application of what marketing strategies are carried out by the company in maintaining the product life cycle. The chosen research method is qualitative descriptive. According to the findings, this company carries out marketing strategies in maintaining products by using product life cycles so that products remain in demand and grow in the market.